2021
DOI: 10.1111/jfpp.16124
|View full text |Cite
|
Sign up to set email alerts
|

Effects of particle sizes on structural and physicochemical properties of pomelo peel powders

Abstract: The structural and physicochemical properties of pomelo peel powders with different particle sizes were investigated. The MasterSizer and scanning electron microscopy observations indicated that three pomelo peel powders with different particle sizes were successfully prepared via jet milling, of which the average diameters (d(90)) were 53.43 ± 0.49, 27.73 ± 0.13, and 20.15 ± 0.17 µm. Fourier‐transform infrared spectroscopy, X‐ray diffraction, and low field nuclear magnetic resonance analysis indicated that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Anhydrous ethanol was adopted as the dispersant, stirring speed was 800 r/min, and determining temperature was 25 °C. The values of D [4,3] , D [3,2] , d (10) , d (50) , d (90) , and the specific surface area were recorded, where D [4,3] is the volume-weighted diameter, D [3,2] is the surface-weighted diameter, and d (10) , d (50) , and d (90) represent the average diameter at which 10%, 50%, and 90% of the particles are smaller, respectively [ 12 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anhydrous ethanol was adopted as the dispersant, stirring speed was 800 r/min, and determining temperature was 25 °C. The values of D [4,3] , D [3,2] , d (10) , d (50) , d (90) , and the specific surface area were recorded, where D [4,3] is the volume-weighted diameter, D [3,2] is the surface-weighted diameter, and d (10) , d (50) , and d (90) represent the average diameter at which 10%, 50%, and 90% of the particles are smaller, respectively [ 12 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Pomelo, a specialty citrus fruit, is abundantly harvested in Fujian Province, China [ 12 , 13 ]. Pomelo fruitlets are mainly generated from the pomelo growth process, the state of hormones in the reproductive organs, and removal of old or young leaves.…”
Section: Introductionmentioning
confidence: 99%
“…fruitlets and commercial MCC as reported previously (Zheng, Hong, et al, 2021). Samples were frozen, sublimated, gilded with current of 40 mA, subsequently observed with SEM under accelerating voltage of 3.0 kV.…”
Section: Sem Observationmentioning
confidence: 99%
“…Pomelo fruitlets contain fiber rather than pulp. In general, it is discarded during cultivation, causing 200,000–350,000 tons of waste every year (He et al, 2022; Zheng, Hong, et al, 2021). Our previous study found that pomelo fruitlets are an ideal raw material to extract cellulose via ultrasonic assisted alkaline hydrogen peroxide hydrolysis, of which the yield is 15.79 ± 1.18% (He et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation